[AcMIm]Cl-Catalyzed One-Pot Multicomponent Synthesis of Pyran Chromene Derivatives - Prasad, Dhaneshwar; Banerjee, Subhash (Synlett, 2025)
A sustainable one-pot multicomponent synthesis of dihydropyrano[3,2-c]chromenes and 2-aminochromenes was developed using [AcMIm]Cl, a task-specific acidic ionic liquid catalyst, under mild, solvent-free conditions. The present protocol affords dihydropyrano[3,2-c]chromenes in excellent yields (93–99%) with a short reaction time (4–5 min), and comparable efficiency was observed for the 2-aminochromenes (90–92%). The bifunctional [AcMIm]Cl bears an acidic carboxyl (–COOH) and a basic imidazolium nitrogen, which act synergistically to activate both the aldehyde carbonyl and the malononitrile C–H bond, thereby accelerating the reaction. The major advantages of this method include a simple workup: no volatile organic solvent, and the solid products were purified by recrystallization from hot ethanol without chromatography. These features render the present method environmentally benign and economically advantageous than conventional approaches.
Keywords: Task-specific ionic liquid; [AcMIm]Cl; Dihydropyrano[3,2-c]chromenes; 2-Aminochromenes; One-pot multicomponent reactions; Green synthesis